Comprehensive Midwife Care For Mrs "T" With Normal Pregnancy In Ujung Loe Public Health Center, Ujung Loe District, Bulukumba Regency - Ely Kurniati; Nurwahida; Andi Tenri Fajriani (Jurnal Life Birth, 2023)
Many factors influence and can be the cause of AKI and IMR, so it is necessary to make more effective efforts than before, namely by conducting continuous midwifery care so that complications starting during pregnancy can be detected as early as possible and given appropriate treatment. This comprehensive midwifery care was given to Mrs. "T" in her third trimester of pregnancy at the Ujung Loe Health Center with the aim of providing comprehensive midwifery care starting during pregnancy, childbirth, newborns, postpartum, neonates, and family planning. The results of comprehensive midwifery care for Mrs "T" carried out independent and collaborative care starting from the period of pregnancy with physiological complaints and progressing normally, in normal delivery with spontaneous delivery, normal newborns, four times respiratory visits, and three times neonates who proceed normally without any complications and the use of 3-month injectable contraception (DMPA). The conclusion of comprehensive midwifery care for Mrs. "T" starting from 36 weeks, three days of gestation, childbirth, newborns, postpartum, neonates, and family planning with 3-month injection KB (DMPA), proceeded normally without complications or complications carried out according to midwifery service standards using a comprehensive and documented SOAP midwifery care management approach. It is hoped that the results of this study can be used as reading material and references for further researchers, adding insight and learning in the implementation of comprehensive midwifery care, implementing comprehensive midwifery care according to standard operating procedure (SOP) in every health service, especially at the Ujung Loe Health Center, Ujung Loe District, Bulukumba Regency and providing awareness to the public. especially the mother regarding her concern for the health condition of her and her fetus so that it can minimize problems or complications that can occur.